Egress of non-enveloped enteric RNA viruses - Owusu, Irene A.; Quay, Osbourne; Passalacqua, Karla D. (Microbiology Society, 2021)
A long-standing paradigm in virology was that non-enveloped viruses induce cell lysis to release progeny virions. However, emerging evidence indicates that some non-enveloped viruses exit cells without inducing cell lysis, while others engage both lytic and non-lytic egress mechanisms. Enteric viruses are transmitted via the faecal–oral route and are important causes of a wide range of human infections, both gastrointestinal and extra-intestinal. Virus cellular egress, when fully understood, may be a relevant target for antiviral therapies, which could minimize the public health impact of these infections. In this review, we outline lytic and non-lytic cell egress mechanisms of non-enveloped enteric RNA viruses belonging to five families: Picor naviridae, Reoviridae, Caliciviridae, Astroviridae and Hepeviridae. We discuss factors that contribute to egress mechanisms and the relevance of these mechanisms to virion stability, infectivity and transmission. Since most data were obtained in traditional two-dimensional cell cultures, we will further attempt to place them into the context of polarized cultures and in vivo pathogen esis. Throughout the review, we highlight numerous knowledge gaps to stimulate future research into the egress mechanisms of these highly prevalent but largely understudied viruses
Keywords: Christiane E. Wobus; University of Ghana; WACCBIP_NCDS; egress; enteric virus; non-enveloped virus; RNA virus